The rising US trade protectionism under Donald Trump and its implication on China’s artificial intelligence advancement - Titi Rahmania Gulo; Ilmi Dwiastuti (President University, 2021)
The primary goal of this paper is to provide insight into the factors that have contributed to the trade war between the United States of America and China, which has been influenced not only by the economic sector but also by AI. Furthermore, in light of China's rising power, which threatens to supplant US supremacy, as well as its ambition to become a global leader in artificial intelligence by 2030, the steps taken by the United States during the Donald Trump administration to maintain its global influence are discussed in this paper. Furthermore, there is an indication that China is aiming to boost its global influence, which will be the focus of this paper with due attention to the national artificial intelligence advancement. The desire for both China and the United States to dominate technology has increased competition between the two countries, as evidenced by the numerous technological innovations developed and released by the two countries in recent years. In addition, the authors will conduct empirical case study research in conjunction with comparative analysis. Thus, to investigates this issue through the lens of threat perception, which also serves as a theoretical framework. Lastly, the authors conclude that the advancement of China’s Artificial Intelligence is perceived as a threat for the US national security especially in military and political sector. Keywords : Artificial Intelligence; Threat Perception; National Security